SEMANTIC CHARACTERISE OF ENGLISH JARGONISMS - Mardanova, Mokhira (Журнал иностранных языков и лингвистики, 2021)
The given article deals with the study of semantic anlysis of English jargonisms .We try to define the differences terms of jargons and slangs with examples with definitions. There given some theories about origin and examples of English jargonisms and their stylistic components, which is being used over the countries.